Rituximab na terapêutica da nefropatia membranosa - José Miguel Alves Ribeiro (2020)
Membranous nephropathy is the most common cause of primary nephrotic syndrome in caucasian adults worldwide. Significant advances in recent years have made it possible to improve knowledge about this glomerular pathology. A recent discovery of autoantibodies directed to antigens present in glomerular podocytes and their subsequent identification, significantly altered the strategies for diagnosis, classification, and treatment of this pathology. Several immunosuppressive therapeutic schemes have been proposed for the treatment of the membranous nephropathy. However, immunosuppressive therapy is still highly debated, mainly due to the variable course of the disease, but also due to significant associated toxicity and costs. The growing knowledge of the role of B cells in the pathogenesis of membranous nephropathy has led to the use of rituximab, an anti-CD20 monoclonal antibody, which has emerged as a safe and effective alternative for the treatment of this pathology. Therefore, this review aims to explore the various therapeutic options available for the treatment of membranous nephropathy, with particular emphasis on the use of rituximab, which according to several authors, should become the first-line therapy in the treatment of this glomerular pathology. Thus, a bibliographic review was carried out, supported by the PubMed / Medline database, where 47 articles were selected. In this, the keywords considered relevant to the present review were the following: "membranous nephropathy", "nephrotic syndrome", "type M phospholipase A2 receptor" (PLA2R), "diagnosis", "prognosis", "treatment" and "rituximab". We conclude that, despite the evidence that already exists regarding the efficacy and safety of rituximab compared to the remaining therapeutic options, more randomized and controlled studies are needed, so that rituximab can be defined as the gold standard treatment for membranous nephropathy.